Quality Assessment of Water Bodies in Selected Mining Communities of Plateau State, Nigeria - , A. O. Owolabi, Z. O. Opafunso (Archives of Current Research International, 2017)
Aims: The study assessed the portability as well as the suitability for use in irrigation of water samples from mine ponds, streams, wells and boreholes of selected cassiterite mine sites in Plateau State of Nigeria. Study Design: Experimental design was used in the sampling and analyses of water samples from different water sources in the study area. Methodology: These samples were analysed using the Atomic Absorption Spectrophotometric (AAS) model AA 6800 in accordance with the provision of ASTMD 856-10 at the Geochemistry Laboratory of the Nigerian Geological Survey Agency (NGSA), Kaduna, Nigeria. Results: The mean pH values of water samples collected from mine ponds, streams, wells and boreholes were 5.6, 6.5, 6.3 and 6.3 respectively. While those of As were 0.027 ppm, 0.013 ppm, 0.013 ppm and 0.013 ppm and those of Cd were. 0.013 ppm, 0.0098 ppm, 0.007 ppm and 0.0079 ppm. The mean concentrations of Cr in water samples collected from mine ponds, streams, wells and boreholes were 0.06 ppm, 0.03 ppm, 0.03 ppm and 0.03 ppm respectively. While those of Pb were 0.06 ppm, 0.02 ppm, 0.02 ppm and 0.03 ppm and the average % Na in the water samples collected from mine ponds, streams, wells and boreholes were 87, 73, 69 and 60 respectively. Conclusion: The water samples collected from the different sources in the study area were acidic and had unenviable amount of toxic contaminants (Cd, Pb and As) in concentrations higher than the maximum allowable limits set by WHO (2011). The consumption of water with high concentrations of Pb for example can lead to mental retardation in children as well as nervous, skeletal, circulatory, enzymatic, endocrine, and immune systems damages while Cd may make the consumers prone to lung cancer, bone fractures, kidney dysfunction, and hypertension. The water samples were also not suitable for irrigation purposes because of the high % Na.